Unbiased profiling of volatile organic compounds in the headspace of Allium plants using an in-tube extraction device. (December 2016) - Kusano, Miyako; Kobayashi, Makoto; Iizuka, Yumiko; Fukushima, Atsushi; Saito, Kazuki
Abstract Background Plants produce and emit important volatile organic compounds (VOCs), which have an essential role in biotic and abiotic stress responses and in plant–plant and plant–insect interactions. In order to study the bouquets from plants qualitatively and quantitatively, a comprehensive, analytical method yielding reproducible results is required. Results We applied in-tube extraction (ITEX) and solid-phase microextraction (SPME) for studying the emissions ofAllium plants. The collected HS samples were analyzed by gas chromatography–time-of-flight–mass spectrometry (GC-TOF–MS), and the results were subjected to multivariate analysis. In case of ITEX-methodAllium cultivars released more than 300 VOCs, out of which we provisionally identified 50 volatiles. We also used the VOC profiles ofAllium samples to discriminate among groups ofA. fistulosum, A. chinense (rakkyo), andA. tuberosum (Oriental garlic). As we found 12 metabolite peaks including dipropyl disulphide with significant changes inA. chinense andA. tuberosum when compared to the control cultivar, these metabolite peaks can be used for chemotaxonomic classification ofA. chinense, tuberosum, andA. fistulosum . Conclusions Compared to SPME-method our ITEX-based VOC profiling technique contributes to automatic and reproducible analyses. Hence, it can be applied to high-throughput analyses such as metabolite profiling.